2018
DOI: 10.3390/su10051433
|View full text |Cite
|
Sign up to set email alerts
|

Security-Constrained Unit Commitment Considering Differentiated Regional Air Pollutant Intensity

Abstract: Conventional environmental-economic power dispatch methods constrain the total amount of emissions of power plants, and they succeed in reducing emissions from the power sector. However, they fail to address the mismatch between emission reductions and the resulting changes in regional air quality. This paper proposes an ecology-and security-constrained unit commitment (Eco-SCUC) model considering the differentiated impacts of generation-associated emissions on regional air quality. A Gaussian puff dispersion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In the study and application of the Gaussian model [17][18][19], some focus is done on the issue of gas diffusion with the known emission source. The default coordinate system is set up taking the emission source as the origin, and the wind direction, and its vertical relations as axes.…”
Section: Gas Spatial Diffusion Modelmentioning
confidence: 99%
“…In the study and application of the Gaussian model [17][18][19], some focus is done on the issue of gas diffusion with the known emission source. The default coordinate system is set up taking the emission source as the origin, and the wind direction, and its vertical relations as axes.…”
Section: Gas Spatial Diffusion Modelmentioning
confidence: 99%
“…The operation of the SCR system is mainly based on the catalyst. When the units are running at low power output, the catalyst is degraded due to the low temperature [28]. At this time, the SCR system needs to be shut down, resulting in a significant increase in emissions.…”
Section: ) Primary Emissions Considering Emission Reduction Measuresmentioning
confidence: 99%
“…To this end, some scholars have established a temporal and spatial distribution (TSD) model of pollutant emissions from power systems, shifting research focus from total pollutant control to optimization of GLC [26] uses the Gaussian plume diffusion model to simulate the diffusion of PM2.5 generated by the power system and incorporates it into the unit combination through differentiated environmental capacity costs. The Gaussian puff model used in [27], [28] is an extension of the Gaussian plume model, which is more suitable for small calm wind weather, and can improve the accuracy of pollutants TSD in haze weather [29] further considered the influence of atmospheric boundary layer (ABL) and attenuation benefits on pollutant dispersion, established a TSD model for various pollutants, and proposed a high-dimensional multi-objective optimization method; Based on this model, [30] developed a multi-objective EED strategy for the power-natural gas integrated energy system. However, the research using pollutant diffusion models to study the environmental benefits of CHP units has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The central theme of the Guo et al paper [15] involves the mismatch between emission reductions and the resulting changes in regional air quality. The authors propose an ecology-and security-constrained unit commitment (Eco-SCUC) model that integrates both air quality intensity (API) and stochastic wind power constraints to improve emissions modeling.…”
Section: Contributions Of Collectionsmentioning
confidence: 99%